Infection of liver sinusoidal endothelial cells with Muromegalovirus muridbeta1 involves binding to neuropilin-1 and is dynamin-dependent - Kyrrestad, Ingelin; Larsen, Anett Kristin; Sánchez Romano, Javier; Simón-Santamaría, Jaione; Li, Ruomei; Sørensen, Karen Kristine (Frontiers in Cellular and Infection Microbiology, 2023)
Liver sinusoidal endothelial cells (LSEC) are scavenger cells with a remarkably high capacity for clearance of several blood-borne macromolecules and nanoparticles, including some viruses. Endocytosis in LSEC is mainly via the clathrin-coated pit mediated route, which is dynamin-dependent. LSEC can also be a site of infection and latency of betaherpesvirus, but mode of virus entry into these cells has not yet been described. In this study we have investigated the role of dynamin in the early stage of muromegalovirus muridbeta1 (MuHV-1, murid betaherpesvirus 1, murine cytomegalovirus) infection in mouse LSECs. LSEC cultures were freshly prepared from C57Bl/6JRj mouse liver. We first examined dose- and time-dependent effects of two dynamin-inhibitors, dynasore and MitMAB, on cell viability, morphology, and endocytosis of model ligands via different LSEC scavenger receptors to establish a protocol for dynamin-inhibition studies in these primary cells. LSECs were challenged with MuHV-1 (MOI 0.2) ± dynamin inhibitors for 1h, then without inhibitors and virus for 11h, and nuclear expression of MuHV-1 immediate early antigen (IE1) measured by immune fluorescence. MuHV-1 efficiently infected LSECs in vitro. Infection was significantly and independently inhibited by dynasore and MitMAB, which block dynamin function via different mechanisms, suggesting that initial steps of MuHV-1 infection is dynamin-dependent in LSECs. Infection was also reduced in the presence of monensin which inhibits acidification of endosomes. Furthermore, competitive binding studies with a neuropilin-1 antibody blocked LSEC infection. This suggests that MuHV-1 infection in mouse LSECs involves virus binding to neuropilin-1 and occurs via endocytosis.